2022
DOI: 10.1039/d2ra05304g
|View full text |Cite
|
Sign up to set email alerts
|

Structural, optical, magnetic, and enhanced antibacterial properties of hydrothermally synthesized Sm-incorporating α-MoO32D-layered nanoplates

Abstract: In this study, we have synthesized pristine and [0.5,1.5, and 2.5] M% samarium (Sm)-incorporating α-MoO3 2D-layered nanoplates utilizing a facile hydrothermal process, and investigated the physical properties along with antibacterial effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 104 publications
0
16
0
Order By: Relevance
“…In order to eliminate ROS, antioxidants are necessary. The antioxidant activity of nanocomposites in vitro indicates their pharmacological function. A recent study showed that the antioxidant activity of synthesized nanocomposites can be analyzed by various methods, but the ABTS assay and the DPPH radical assay are considered to be the most reliable methods. The antioxidant activity of the biogenically synthesized nanocomposite against ABTS free radical cations was analyzed, and ascorbic acid was used as the standard. Initially, ABTS •+ free radical cations are formed due to the removal of electrons from nitrogen.…”
Section: Resultsmentioning
confidence: 99%
“…In order to eliminate ROS, antioxidants are necessary. The antioxidant activity of nanocomposites in vitro indicates their pharmacological function. A recent study showed that the antioxidant activity of synthesized nanocomposites can be analyzed by various methods, but the ABTS assay and the DPPH radical assay are considered to be the most reliable methods. The antioxidant activity of the biogenically synthesized nanocomposite against ABTS free radical cations was analyzed, and ascorbic acid was used as the standard. Initially, ABTS •+ free radical cations are formed due to the removal of electrons from nitrogen.…”
Section: Resultsmentioning
confidence: 99%
“…Sm-g-C 3 N 4 improved the bactericidal efficiency by enhancing a positive charge on the catalyst surface that interacts with an oppositely charged membrane, causing membrane destruction, as shown in Figure S3. 16,49 According to systematic research, oxygen vacancy has a significant impact on bactericidal activity. 52 The influence of the α-MoO 3 nanostructures enhanced the antimicrobial effect due to their ability to produce ROS.…”
Section: Resultsmentioning
confidence: 99%
“…15 Additionally, metal oxides are extensively well known for their antimicrobial activity among the massive nanoparticles synthesized. 16 Among the metal oxides mentioned above, molybdenum trioxide (MoO 3 ) has pale yellow or blue mixed-gray colored nanoparticles. MoO 3 is a semiconducting material of the n-type having a significant band gap (ranging from 2.8 to 3.2 eV) that has several possible applications, 15 including catalysis, sensors, batteries, photography, display devices, and lubricants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, structural changes are verified by the changes of lattice parameters shown in Tables S1-S3, † by considering the highest intensity crystalline plane (020) of α-MoO 3 . 31 Calculation procedures are presented in the ESI. †…”
Section: Paper Dalton Transactionsmentioning
confidence: 99%